A Catholic sister's experiences of leadership and ministry as a faculty member in public higher education. Issue 3 (3rd July 2019) - Delmas, Peggy M.; Ivankova, Nataliya V.
Abstract: This qualitative case study explores the leadership and ministry experiences of a Catholic sister serving as a faculty member in a predominantly male department at a public research university. The study addresses the gap in the literature regarding experiences of women who are members of a religious community and a university faculty. The study highlights the issues of gender, religious identity, culture, and experiences and perceptions of others as they relate to the leadership and ministry experiences of this Catholic sister. Findings reveal the need for the academy to evaluate how and for whom it promotes social good.